Molecular mechanisms and physiological functions of autophagy in kidney diseases - Yang, Jingchao; Yuan, Longhui; Liu, Fei; Li, Lan; Liu, Jingping; Chen, Younan; Lu, Yanrong; Yuan, Yujia (Frontiers in Pharmacology, 2022)
Autophagy is a highly conserved cellular progress for the degradation of cytoplasmic contents including micromolecules, misfolded proteins, and damaged organelles that has recently captured attention in kidney diseases. Basal autophagy plays a pivotal role in maintaining cell survival and kidney homeostasis. Accordingly, dysregulation of autophagy has implicated in the pathologies of kidney diseases. In this review, we summarize the multifaceted role of autophagy in kidney aging, maladaptive repair, tubulointerstitial fibrosis and discuss autophagy-related drugs in kidney diseases. However, uncertainty still remains as to the precise mechanisms of autophagy in kidney diseases. Further research is needed to clarify the accurate molecular mechanism of autophagy in kidney diseases, which will facilitate the discovery of a promising strategy for the prevention and treatment of kidney diseases.